Caracterização e avaliação da citocompatibilidade de nanocompositos baseados em celulose bacteriana e fibroína para aplicação em regenração tecidual - Barud, Hélida Gomes de Oliveira [UNESP] (2014)
Tissue engineering has the purpose of developping therapeutic options especially designed to be used on limited clinical conditions, aiming to replace or regenerate damaged tissues applying biomaterials for that. The method is based on the cultivation of cells on a matrix or scaffold that should be optimized to offer minimum risk of infections and allow the release of bioactive molecules at the desired location. The success of the methodology depends on Biomaterials’ properties that can be manipulated to mimic the three-dimensional architecture of native tissues extracellular matrix. Thus, we purpose to prepare a new nanocomposite based on bacterial cellulose (BC) / fibroin (SF) aiming at applications in the process of tissue regeneration in dentistry. Three different material’s compositions were prepared (BC/SF 25 % BC/SF 50 % and BC/SF 75 %) and all of them were characterized by thermogravimetric analysis, Vibrational Spectroscopy in the Infrared Region (FT-IR), X-ray diffraction, and Scanning Electron Microscopy (SEM). The material showed good physical and chemical stability including resistance to thermal degradation at high temperatures. The investigation of the cytocompatibility was realized just using the samples BC/SF 50 % and the in vitro tests conducted were MTT, Trypan Blue, cell adhesion and proliferation assays. The statistical analysis was done applying the software Graph Pad Prism 5.0. The results showed that the developed nanocomposite is biocompatible and non-cytotoxic. SEM images revealed a greater number of cells attached to the scaffold CB / FB surface when compared to pure CB scaffolds. Based on the data obtained, it is possible to suggest that the nanocomposite based on CB/FB50% configures an excellent alternative as a scaffold for tissue repair.